1998
DOI: 10.1177/002076409804400406
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Consumer Participation in Mental Health Services: Are Attitudes Related To Professional Orientation?

Abstract: This study describes the development of the Consumer Participation Questionnaire to measure consumer involvement in the planning, management and evaluation of mental health services, and the attitudes of mental health workers towards consumer participation. Results indicate that while most professionals view the concept positively, progress may be occurring faster at the level of individual treatment than at the organisational level. Professionals with a more biological (as opposed to psychosocial) orientation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
85
1
7

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(102 citation statements)
references
References 28 publications
9
85
1
7
Order By: Relevance
“…The results of the our survey mirror the findings of Kent and Read, 49 which showed that most mental health professionals viewed SUI positively. Kent and Read's study highlighted that professionals from psychosocial backgrounds were more likely to predict and associate benefits with user involvement than professionals with a more biological/medical background.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The results of the our survey mirror the findings of Kent and Read, 49 which showed that most mental health professionals viewed SUI positively. Kent and Read's study highlighted that professionals from psychosocial backgrounds were more likely to predict and associate benefits with user involvement than professionals with a more biological/medical background.…”
Section: Discussionsupporting
confidence: 85%
“…We saw also that front-line staff were mostly supportive of user involvement activities and that they particularly welcomed user involvement in training. The prediction that social workers would be more positive than those with a nursing background was borne out and is consistent with the work of Kent and Read, 49 although the context of the two studies is quite different.…”
Section: The Involvement Of 'Ordinary' Service Userssupporting
confidence: 77%
See 1 more Smart Citation
“…The active and direct involvement of users in their own treatment increases the feeling of personal responsibility for changes in the course of treatment and can lead to better therapeutic outcomes including increased self-esteem and coping potential (Delsignore et al 2008;Kent andRead 1998, citing Farina andFisher 1982;Garber and Seligman 1980;Greenfield et al 1985;Schwarzer 1992;Nelson and Borkovec 1989;Lefley 1990;Soffe et al 2004). Sometimes just the opportunity to talk, combined with the experience of being heard, can be a relief for users (Lewis 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Ces dernières sont en effet souvent perçues comme étant trop émotives pour participer aux processus décisionnels (Kent & Read, 1998) ou, encore, n'ayant pas les connaissances nécessaires pour le faire ; on les voit comme des observateurs plutôt que comme des acteurs.…”
Section: Participation Publique Et Santé Mentaleunclassified